Research on the Teaching Model of “Position, Course, Competition, Certification and Creation” in Vocational New Media Operation Courses - LiuRong; WuLiSa (Journal of Exploration of Vocational Education, 2026)
Focusing on the reform of teaching models for the Vocational Education course “New Media Operations”. Addressing current issues such as outdated teaching content, fragmented skills training, and insufficient industry-education integration, it proposes a five-pronged teaching model integrating “position, courses, competitions, certification, and creation”. This model takes job competencies as its starting point, with course instruction at its core, skills competitions as its driving force, professional certification as its benchmark, and innovation and entrepreneurship as its extension. Guided by the principles of ‘aligning specialisms with industry, teaching with job roles, competencies with standards, and prioritising student development,’ it systematically reconstructs course objectives, content, and implementation pathways. Research has designed a project-based curriculum system spanning the entire operational lifecycle, implementing a five-step teaching methodology: task introduction, knowledge acquisition, practical training, outcome presentation, and reflective refinement. A collaborative mechanism has been established linking courses to job roles, integrating competitions with teaching, merging certification with curricula, and linking courses with innovation initiatives. Practice demonstrates that this model effectively enhances students’ comprehensive professional competencies, certification attainment rates, competition award levels, and entrepreneurial practice outcomes. Concurrently, it facilitates teacher transformation and curriculum enrichment, providing a replicable and scalable teaching reform paradigm for higher vocational new media programmes.